1970
DOI: 10.1083/jcb.45.2.367
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASTRUCTURE OF BACTERIZED AND AXENIC TROPHOZOITES OF ENTAMOEBA HISTOLYTICA WITH PARTICULAR REFERENCE TO HELICAL BODIES

Abstract: Electron microscopy of bacterized and axenic trophozoites of Entamoeba histolytica showed only slight differences in ultrastructure between the two . As with other species of Entamoeba so far studied, this species lacks typical mitochondrial structures and formed endoplasmic reticulum . Dense clusters of glycogen particles are especially characteristic in axenic amebas . Microtubular structures 360 A in diameter appear randomly oriented in both bacterized and axenic trophozoites . Ribonucleoprotein (RNP) bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
24
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 25 publications
6
24
1
Order By: Relevance
“…This conclusion is in conflict with earlier reports that E. histolytica lacks a continuous ER compartment, which were based on work conducted with fixed amebic trophozoites (6,8,11,13,16). The inability to detect a continuous ER compartment in prior studies presumably was an artifact of fixation.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…This conclusion is in conflict with earlier reports that E. histolytica lacks a continuous ER compartment, which were based on work conducted with fixed amebic trophozoites (6,8,11,13,16). The inability to detect a continuous ER compartment in prior studies presumably was an artifact of fixation.…”
contrasting
confidence: 55%
“…Beyond its medical importance, E. histolytica has several unusual features that are of interest to evolutionary biologists. It is a structurally simple eukaryote, lacking mitochondria and peroxisomes and having no recognizable Golgi complex or rough endoplasmic reticulum (ER) (6,11,16). Some have hypothesized that E. histolytica diverged from other eukaryotic lineages prior to the development of these structures (2).…”
mentioning
confidence: 99%
“…Comparison of arrays seen in longitudinal and cross sections showed the ordering of helices to be the same in both trophozoites and cysts. There was no evidence that helices formed at specific sites in the cell or about microfilaments, as has been suggested by others (22,12,19).…”
Section: Inhibitor-stim Ulated Ribosome Aggregationmentioning
confidence: 50%
“…We have noted in the literature and in our own studies a correspondence between the appearance of aggregates in trophozoites and periods of reduced metabolic activity. For example, in one report (1) the number of aggregates was seen to increase with culture age, and in another (22), slow-growing trophozoites were found to contain more helical arrays than rapidly growing cells, in our own work we have observed that particles with the staining properties of chromatoid bodies frequently appear in trophozoites which have entered stationary growth phase and disappear when the amebas are transferred to fresh growth medium. Of course, in cysts, which probably represent the metabolic ebb in the Entamoeba life cycle, virtually all the ribosomes are aggregated (2, 13).…”
mentioning
confidence: 72%
“…As ancient eukaryotes, Entamoeba parasites contain only rudimentary endoplasmic reticulum and Golgi apparatus (2,3). Despite this, vesicle trafficking pathways appear to be essential to the pathogenesis of these parasites as (i) uptake and digestions of nutrients by mature trophozoites in the large intestine, (ii) invasion of the intestinal epithelium, (iii) delivery of cyst wall components during encystation, and (iv) dissemination and establishment of extra-intestinal infections all rely on endocytosis and secretion.…”
mentioning
confidence: 99%